Heavy hands, helping hands, holding hands: the politics of exclusion in victims’ networks in Nepal - Sajjad, Tazreena (International journal of transitional justice, 2016)
In recent years, attention has been paid in scholarship and practice to the need for ‘victim-centeredness’ in transitional justice (TJ) programming. Despite this, transitional mechanisms often underappreciate or obscure the critical dimensions of agency, the complexities within and between victim-centered mobilization and the experiences of such networks with TJ processes. Furthermore, they fail to capture victims’ experiences as political actors, while promoting an understanding of this group as a single, indivisible whole. This article engages with contentious dynamics within the victim landscape through a case study of Nepal, raising critical questions about who constitutes the terrain of victims, who has a role in the design of TJ mechanisms and how international involvement has created opportunities and constraints in a diverse landscape of victims’ networks. It also calls for a deeper examination of how, within a global context of norm dispersion, the persuasive power of transnational advocacy networks and the expansion of the TJ discourse, victim-centered advocacy remains largely ignored as a political force. The article argues that neglecting the complex realities of victimhood, compounded by the dominance of standardizing global norms, institutionalized structures such as truth commissions and the prominence of the ‘elite’ local’s concerns, can alienate and even delegitimize grassroots victim-centered activism or reduce consultations with such groups to a form of tokenism. In so doing, the elite drivers of TJ processes continue to define the parameters of victimhood.